PEMODELAN BAWAH PERMUKAAN BANTAR KARET, JAWA BARAT MENGGUNAKAN METODE GRAVITASI - Jamaluddin Jamaluddin; Maria Maria; Hamriani Ryka; Rohima Sera Afifah (JURNAL GEOCELEBES, 2019)
Gravity method is one of the geophysical methods that is often used to obtain information about the subsurface through differences density of the rocks around it. Gravity anomaly data used in this study is primary data that has been processed data. Data processing is obtained by reducing gravity observation data until complete bouguer anomaly values. The results of the interpretation of the gravity anomaly show that the types of rocks in subsurface of the study area are peridotite, tuff, riolite and basalt. The rock with the highest density is peridotite with a density value of 3.15 gr/cm3. This is due to the intrusion process to forming peridotite and there are two zones boundaries which have very significant density differences.